Aquaculture of the stalked barnacle Pollicipes pollicipes: improving farming techniques in an extensive system located in Sines (Portugal) - Darras, Jérôme Pierre Joseph (2018)
Dissertação de mestrado, Aquacultura e Pescas, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2017